2014
DOI: 10.1002/rcm.6934
|View full text |Cite
|
Sign up to set email alerts
|

Electron attachment to some naphthoquinone derivatives: long‐lived molecular anion formation

Abstract: NI lifetime measurements by means of a modified DEAS instrumentation can provide quantitative data of EA. A simple Arrhenius approximation seems to be adequate to describe the process of electron detachment from molecular anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 56 publications
1
27
0
8
Order By: Relevance
“…A number of recent theoretical studies, on systems that are known to exhibit long-lived anions in the gas phase, have supported this contention by highlighting that the above-threshold resonances of shape character have broad electron acceptance windows. [93][94][95] Experimentally, such a broad window to electron attachment dynamics has been observed across a range of PAH and PAHlike systems, 22,30,38 and has been implied in the present study by virtue of thermionic emission observed at all photoexcitation energies. The broad electron acceptance window arises from a combination of a high density of resonances (increases with increasing PAH size) each with a broad spectral width due to their inherent short lifetimes (e.g.…”
Section: Role Of Non-adiabatic Dynamics In Astrochemistrysupporting
confidence: 65%
“…A number of recent theoretical studies, on systems that are known to exhibit long-lived anions in the gas phase, have supported this contention by highlighting that the above-threshold resonances of shape character have broad electron acceptance windows. [93][94][95] Experimentally, such a broad window to electron attachment dynamics has been observed across a range of PAH and PAHlike systems, 22,30,38 and has been implied in the present study by virtue of thermionic emission observed at all photoexcitation energies. The broad electron acceptance window arises from a combination of a high density of resonances (increases with increasing PAH size) each with a broad spectral width due to their inherent short lifetimes (e.g.…”
Section: Role Of Non-adiabatic Dynamics In Astrochemistrysupporting
confidence: 65%
“…На первом этапе эксперимента записывают кривую эффек-тивного выхода M −· , т. е. ток молекулярных ОИ как функцию энергии электронов ε. Затем на систему откло-нения перед входом в умножитель подают отклоняющий потенциал для удаления заряженной компоненты пучка исследуемых частиц и регистрируют сигнал нейтраль-ных частиц M 0 , образовавшихся при автоотщеплении электронов от M − за время дрейфа молекулярных ОИ во второй бесполевой области. Для ионов SF −· 6 /SF 6 (m/e = 146) время пролета бесполевой области до по-падания в систему регистрации равно 6 µs. Эта величина известна с высокой точностью, поскольку определяется величиной ускоряющего потенциала на источнике ионов (−4 kV) и расстоянием от выхода из магнита до входа в умножитель (40 cm).…”
Section: экспериментunclassified
“…Поскольку раскрытие протекает путем преодоления потенциального барьера высотой 0.65 eV, " эффективное сродство" открытой структуры оказыва-ется равным 1.14 eV [5]. В работе [5] было показано, что наблюдаемое время жизни ионов M −· фталида, равное ∼ 100 µs (считается, что погрешность измерения этой величины лежит в пределах 10−15%), хорошо воспроизводится в рамках простой аррениусовской мо-дели [6]:…”
Section: Introductionunclassified
“…Насколько известно авторам, выброс двух атомов водорода из ОМИ наблюдается (при низких энергиях электронов) лишь в тех случаях, когда молекула-мишень имеет определённую структуру: либо содержит несколько гидроксильных групп (полифенол) [11,12,33], либо существует возможность внутренних вращений одних частей молекулы по отношению к дру-гим, при которых происходит сближение атомов водо-рода [34]. В обоих случаях необходимо, чтобы в качестве нейтрального фрагмента образовалась молекула водо-рода: только при таком условии удаётся объяснить факт наблюдения анионов [M -2H] -при низких (вплоть до тепловых) энергиях электронов.…”
Section: ние фрагментов [M -2h]unclassified
“…В первом случае эффективность антиоксидантного действия должна коррелировать с энергией разрыва ОН-связи, тогда как во втором -с по-тенциалом ионизации полифенольной молекулы. Вме-сте с тем, известно, что большую роль в противоради-кальной активности играют определённые структурные элементы (взаимное расположение ОН-групп) [7,10], а сами молекулы полифенолов обладают также выражен-ными электрон-акцепторными свойствами [11,12], при этом, полная картина их комплексного действия на орга-низм далека от понимания [13].…”
Section: Introductionunclassified